Escherichia coli mutants defective in the uncH gene. - Humbert, R (1983)
Plasmids carrying cloned segments of the unc operon of Escherichia coli have been used in genetic complementation analyses to identify three independent mutants defective in the uncH gene, which codes for the delta subunit of the ATP synthetase. Mutations in other unc genes have also been mapped by this technique. ATPase activity was present in extracts of the uncH mutants, but the enzyme was not as tightly bound to the membrane as it was in the parental strain. ATP-dependent membrane energization was absent in membranes isolated from the uncH mutants and could not be restored by adding normal F1 ATPase from the wild-type strain. F1 ATPase prepared from uncH mutants could not restore ATP-dependent membrane energization when added to wild-type membranes depleted of F1. Membranes of the uncH mutants were not rendered proton permeable as a result of washing with low-ionic-strength buffer.